Critical Psychology and Cultural Psychology: Common Concerns – Divergences – Productive Linkages - Maiers, Wolfgang (International Review of Theoretical Psychologies, 2026)
Standing in the tradition of the Cultural-Historical School, which is unanimously recognised as an essential contribution to cultural psychology, German Critical Psychology is also repeatedly attributed to this field. Although commonalities undoubtedly exist between the subject-scientific perspective of the latter and cultural-psychological views, characteristic differences must also be highlighted – and this also concerns the reception of Vygotsky’s and his collaborators’ work: Both the Cultural-Historical and the Critical-Psychological approaches oppose any ‘culturalist’ dissolution of the materialist concept of societal relations/practice into either fuzzy or straightforwardly idealistic notions of culture as a system of linguistic-symbolic meanings, and any dichotomisation between the naturalness and the societality of human development of consciousness. Marxist Critical Psychology focuses on the capitalist mode of production and life with its class-specific, intersectional relations of inequality, oppression, and discrimination, which determine cultural processes and involve a contradictory interplay of possibilities and restrictions of personal agency – structural relationships that are easily ignored in idealistic (e.g. social constructivist or discourse-theoretical) conceptions of culture. When framed in a materialist way, the concept of culture can, in turn, enrich our concept of society with an action-relevant dimension by opening access to the actors' perspective on the diversity and mutability of socio-cultural codifications of life-worlds and subjectivities. In this respect, cultural theories refer to a level of research that is basically laid out, but not yet sufficiently differentiated in Critical Psychology. In order to achieve this concretisation, further elaboration of a Marxist concept of culture is needed, from which existing cultural theories can be reinterpreted and coherently integrated.